Between the Abuser and the Street: An Intersectional Analysis of Housing Challenges for Abused Women - Little, Margaret (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2015)
This article provides an overview of the limited housing options available for abused women in Canada. The author explores the erosion of a commitment to housing for Canada’s marginalized, the need for an intersectional analysis to fully appreciate the impact of this erosion, and then addresses the results: the exceedingly limited housing possibilities for abused women (shelters, second and third stage housing, social housing and the private market). The author draws upon qualitative interviews with abused women; government and non-governmental agency reports to argue that abused women in Canada, especially those marginalized by race and colonialism, have few alternatives between their abuser and living on the street. Résumé Cet article fourni un aperçu des options de logement limitées disponibles pour les femmes violentées au Canada. L’auteur explore l’érosion de l’engagement au logement pour les personnes les plus marginalisées au Canada, et la nécessité d’une analyse intersectionelle afin de bien comprendre l’impact de cette érosion. Le résultat de cette analyse est inévitablement que les possibilités de logement sont extrêmement limitées pour les femmes violentées (les abris, les refuges de deuxième et troisième étapes, le logement social, et le marché immobilier privé). L’auteur utilise des entrevues qualitatives avec des femmes violentée et des rapport gouvernementaux et d’organisations non-gouvernementales pour démontrer que pour les femmes violentées au Canada, surtout celles qui sont également marginalisées par la race et le colonialisme, il existe peu d’alternatives entre leurs abuseur et vivre dans la rue. Mot-Clefs: violence domestique; pauvreté genrée; discrimination; politique de logement.